A review on various security attacks in vehicular ad hoc networks - Mustafa Maad Hamdi; Lukman Audah; Mohammed Salah Abood; Sami Abduljabbar Rashid; Ahmed Shamil Mustafa; Hussain Mahdi; Ahmed Shakir Al-Hiti (Institute of Advanced Engineering and Science, 2021)
Ad hoc vehicle networks (VANET) are being established as a primary form of mobile ad hoc networks (MANET) and a critical infrastructure to provide vehicle passengers with a wide range of safety applications. VANETs are increasingly common nowadays because it is connecting to a wide range of invisible services. The security of VANETs is paramount as their future use must not jeopardize their users' safety and privacy. The security of these VANETs is essential for the benefit of secure and effective security solutions and facilities, and uncertainty remains, and research in this field remains fast increasing. We discussed the challenges in VANET in this survey. Were vehicles and communication in VANET are efficient to ensure communication between vehicles to vehicles (V2V), vehicles to infrastructures (V2I). Clarified security concerns have been discussed, including confidentiality, authentication, integrity, availableness, and non-repudiation. We have also discussed the potential attacks on security services. According to analysis and performance evaluations, this paper shows that the ACPN is both feasible and appropriate for effective authentication in the VANET. Finally, the article found that in VANETs, encryption and authentication are critical.